Innovative activity of small and medium-sized businesses in the context of digital transformation of the economy - V. E. Deryzemlya (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the dynamics of indicators of innovation activity of small and medium-sized businesses in the conditions of digitalization of the economy. The analytical data of the state support of innovative processes of small and medium-sized businesses, consisting in subsidizing their activities, including those aimed at the formation of digital culture in the country, are presented. According to the results of the study, the elements of the innovation process of small and medium-sized businesses are reflected as an object of transformation of the basic concept of the innovation process of companies.